Community engagement in Citrus sudachi harvesting: Implementing good handling practices for post-harvest optimization - Fidia Fibriana; Wiyanto Wiyanto; Arif Widiyatmoko; Andhina Putri Heriyanti; Kaylha Salsabilla Nurazizah; Ahmad Firman Syah (ABDIMAS DEWANTARA, 2026)
Sudachi citrus is a valuable commodity with the potential to support local and global food security. However, post-harvest handling challenges often hinder its quality and yield.  This community engagement program aimed to optimize Sudachi harvesting practices in Oi-Cho, Anan City, Tokushima Prefecture, Japan, by implementing Good Handling Practices (GHP). In collaboration with international NGOs, i.e., Dejavato Foundation and NICE Japan, the program involved international work campers and residents in adopting effective GHP methods focused on improving harvesting, storage, and distribution techniques. The initiative improved harvesting technique and hygiene compliance among participants, and introduced a product diversification strategy to reduce post-harvest waste from lower-grade fruit, aligning directly with Sustainable Development Goal (SDG) 2, which seeks to end hunger and promote sustainable agriculture. Furthermore, the program exemplifies SDG 17 by fostering inclusive, cross-border partnerships that leverage community-based innovation and knowledge exchange. Ultimately, this program achieved a strategic step toward sustainable Sudachi production and harvesting, as well as strengthens international collaboration through participatory, grassroots engagement.